Tafsir Al-Qurâan Al-MajidâAl-Nurâ Karya T.M.Hasbi Ash- Shiddieqy (Corak Tafsir berdasarkan Perkembangan Kebudayaan Islam Nusantara) - Miswar, Andi (Fakultas Adab dan Humaniora UIN Alauddin, 2015)
Tafsir al-Qurâan al-Majid âal-Nurâ is a work by T.M.Hasbi Al-Siddieqy, by applying tahlili writing method with tafsir fiqh characteristic, this work is present to meet the demands of Islamic culture development in Indonesia. With Indonesia nuanced interpretation (tafsir) provides convenience for those who do not understand Arabic well, so it can lead Indonesian people practicing the Quran and the Hadith, for the development of religion and nation.